Karbala in London: Battle of Expressions of Ashura Ritual Commemorations among Twelver Shia Muslims of South Asian Background - Dogra, Sufyan Abid (Journal of Muslims in Europe, 2017)
The roots of the struggle for authority among various groups of Twelver Shias of South Asian background living in London revolves around the idea of what is ‘true and authentic’ Shia Islam. The theological and political genealogy of this power struggle can be traced by examining the history of Shia Islam in South Asia. This article provides historical analyses and ethnographic accounts of Shia Islam and how it is practised in London. It investigates the influence of London-based Iranian and Iraqi Shia transnational networks on South Asian Hussainias and those who attend them. While some London-based Shias of South Asian origin conform to the Iran-backed reformist versions of globally standardised ritual commemoration of Ashura, others detest this and search for religious reinterpretations that assert South Asian ways of commemorating the Ashura ritual.